Efektivitas dan Kontribusi PAD dan Dana Perimbangan Terhadap APBD Kabupaten Lamongan: (Efektivitas dan Kontribusi PAD dan Dana Perimbangan Terhadap APBD Kabupaten Lamongan) - Sabrina, Firistya; Nurul Hanifa (Jurnal Ekonomika : INDEPENDEN, 2025)
This research is motivated by fluctuations in Lamongan Regency's Original Regional Income (PAD), which often does not reach targets, high dependence on Balancing Funds, and the impact of the pandemic on the regional economy. This research aims to determine the level of effectiveness of PAD and Balancing Funds in implementing the APBD, as well as analyzing the magnitude of their contribution to the total APBD of Lamongan Regency. Using quantitative descriptive methods with secondary data from the APBD Realization Report for the 2019-2023 period, the research results show that the effectiveness of PAD reached an average of 103.91% (very effective) and the Balancing Fund was 96.95% (effective). However, PAD's contribution to the APBD is still low with an average of 16.63%, while the Balancing Fund contributes significantly at 55.72%. This condition indicates the need to increase regional fiscal independence even though the level of effectiveness of financial management is already good.